Mechanical properties of hybrid fibre reinforced composite concrete - Ghazali, Mohd. Izaan (2014)
This study focusses on the experimental investigation carried out on Hybrid Fibre Reinforced Composite Concrete (HyFRCC) which is the combination between industrialized steel fibre and polypropylene synthetic fibre for total fibre volume fraction of 1.0 % from the volume of concrete. The objective of this study is to determine the mechanical properties of hybrid fibre reinforced composite concrete. Plus, the best proportion of HyFRCC can be determined from the optimum strength of concrete. The mechanical properties of concrete grade 30 for the compressive strength, flexural strength, tensile splitting strength, toughness and modulus of elasticity were studied with proportion of 100-0, 75-25, 50-50, 25-75, 0-100 of steelpolypropylene respectively. The mechanical properties of concrete with and without fibre were determined in a comparative way based on percentage differences. The obtained results with the optimum mix designation 72-25 of steelpolypropylene fibres confirm that hybridization concept which has been introduced to concrete has improved the performance of plain concrete in term of compression, flexural, tensile strength, Modulus of Elasticity and its energy absorption